Overview on antimicrobial prescription habits in cats at different clinical services of the Veterinary Teaching Hospital of Parma - Francesca Fidanzio; Martina Rega; Simone Bertini; Alicia Maria Carrillo Heredero; Andrea Corsini; Francesca Corti; Serena Crosara; Cecilia Quintavalla (BMC Veterinary Research)
Abstract Antimicrobials are frequently administered for therapeutic and prophylactic purposes in companion animals. Their use is closely monitored as related to antimicrobial resistance both in human and veterinary medicine. This retrospective study aimed to describe antimicrobial prescription by different clinical services in cats visited at the Veterinary Teaching Hospital of the University of Parma (VTH-UP) between January 2021 and December 2023. The antibiotic classes were divided according to the categorization of antibiotics adopted by the European Medicines Agency (EMA); EMA categories A and B were classified as Critically Important Antimicrobials (CIAs). Overall, 43.8%, 35.0%, and 35.0% of visited cats received an antimicrobial prescription in 2021, 2022, and 2023, respectively. Most of the prescriptions were Category C “Caution” antibiotics (49.0%, 54.0%, and 55.0% in 2021, 2022, and 2023, respectively). Category B “restrict” antibiotics represented 13.0%, 12.0%, and 11.0% of the total antimicrobials prescribed in 2021, 2022, and 2023, respectively. Penicillins associated with beta-lactam inhibitors were the most common antibiotics prescribed each year at the VTH-UP (32.0%, 31.3%, and 23.7% of total prescriptions in 2021, 2022, and 2023, respectively). Among CIAs, quinolones were the most common, with 12.1%, 11.2%, and 10.1% of the total prescriptions in 2021, 2022, and 2023, respectively. Culture and sensitivity tests (CSTs) were performed for 18.1% (85/470), 17.4% (73/420), and 23.0% (96/417) of the total prescriptions in 2021, 2022, and 2023, respectively. Considering only CIA prescriptions, CSTs were performed in 70.0% (49/70), 66.7% (38/57), and 70.9% (39/55) of CSTs in 2021, 2022, and 2023, respectively. Antimicrobial use varies considerably depending on the clinical service. The use of “restrict” antibiotics was very limited, and attention should be given to therapeutic and prophylactic use.